2023
DOI: 10.1186/s12886-022-02746-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with Diabetes retinopathy among type 2 diabetic patients at Northwest Amhara Comprehensive Specialized Hospitals, Northwest Ethiopia 2021

Abstract: Introduction The worldwide prevalence of Diabetic Retinopathy was recently estimated to be 34.6%. The prevalence of diabetic retinopathy in developed nations has been thoroughly investigated, and risk factors are well understood. However, there is a shortage of information in the study areas about the prevalence and contributing factors of diabetic retinopathy among type two diabetes patients. Objective The aim of this study was to assess the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Despite significant achievements in early diagnosis and therapy, diabetic retinopathy is currently the major cause of blindness and visual impairment in working-age adults worldwide [ 2 ], causing an increased burden on national healthcare systems worldwide [ 3 ]. The prevalence of diabetic retinopathy is estimated to be 27.0% in diabetic patients, which leads to 0.4 million incidences of blindness in the world [ 4 ]. The World Health Organization (WHO) Universal Eye Health: A Global Action Plan 2014–2019 outlines the need to achieve a reduction in the prevalence of avoidable visual impairment and blindness, including that related to diabetes, which is currently among the five most common causes of both moderate or severe visual impairment and blindness [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant achievements in early diagnosis and therapy, diabetic retinopathy is currently the major cause of blindness and visual impairment in working-age adults worldwide [ 2 ], causing an increased burden on national healthcare systems worldwide [ 3 ]. The prevalence of diabetic retinopathy is estimated to be 27.0% in diabetic patients, which leads to 0.4 million incidences of blindness in the world [ 4 ]. The World Health Organization (WHO) Universal Eye Health: A Global Action Plan 2014–2019 outlines the need to achieve a reduction in the prevalence of avoidable visual impairment and blindness, including that related to diabetes, which is currently among the five most common causes of both moderate or severe visual impairment and blindness [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetic retinopathy in our study was 18.1% (95% CI: 11.9-26.5) similar to the prevalence of DR reported by Sivaprasad S et al 16 which had 17.4% (95% CI 15.1%, 19.7%). In another study by Zegeye AF et al, 17 the prevalence was high at 36.3% (95% CI:29.8-47.6).…”
Section: Discussionmentioning
confidence: 85%
“…Numerous statistical studies conducted across the globe reveal the fact that diabetic retinopathy has acted as a significant public health issue in the present society. As per the data of 2023, the prevalence of diabetic retinopathy is estimated to be 34.6% 1 . The 74th World Health Organization (WHO) study revealed that more than 420 million people had diabetes in 2021, and 578 million were predicted to have the disease by 2030.…”
Section: Introductionmentioning
confidence: 95%